Setting the agenda : the news media and public opinion - McCombs, Maxwell E., 1938-; Valenzuela, Sebastián (Polity, 2021)
An anticipated third edition of the go-to next on agenda-setting.
Keywords: masmédia -- sociální aspekty; vliv médií; teorie médií; zpravodajství; mediální politika; mass media -- social aspects; media influence; media theory; reporting; mass media policy; monografie; monographs